(untitled) (Hematology Meeting Reports, 2009)
Little is known about the aetiology of myelodisplastic syndromes/acute myeloid leukemia (MDS/AML). Several factors could play a role in the development of these diseases. Apart from recognized risk factors as alkykating agents, ionizing radiation and benzene, some others have been suggested by few epidemiological published studies (environmental and occupational exposures and lifestyle factors). In this article the currently known risk factors for MDS/AML are reviewed. The better knowledge of their importance in leukemogenesis could lead in the future to improve the prevention of these diseases.